2014
DOI: 10.1534/genetics.113.158766
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Cuticular Protein,BmorCPR2, Alters Larval Body Shape and Adaptability in Silkworm,Bombyx mori

Abstract: Cuticular proteins (CPs) are crucial components of the insect cuticle. Although numerous genes encoding cuticular proteins have been identified in known insect genomes to date, their functions in maintaining insect body shape and adaptability remain largely unknown. In the current study, positional cloning led to the identification of a gene encoding an RR1-type cuticular protein, BmorCPR2, highly expressed in larval chitin-rich tissues and at the mulberry leaf-eating stages, which is responsible for the silkw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 53 publications
3
55
0
Order By: Relevance
“…In a similar fashion, the corresponding genes in B. mori ( BmCPR2-5 ) were among the top expressing genes during the pre- and post-molt 5 th instar larval stage (Okamoto et al, 2008). Recently, Qiao and coworkers (2014) identified BmCPR2 as the gene responsible for the stony mutant in B. mori . This mutation lead to significant defects in cuticle extension, tensile strength, larval mobility, and body shape.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar fashion, the corresponding genes in B. mori ( BmCPR2-5 ) were among the top expressing genes during the pre- and post-molt 5 th instar larval stage (Okamoto et al, 2008). Recently, Qiao and coworkers (2014) identified BmCPR2 as the gene responsible for the stony mutant in B. mori . This mutation lead to significant defects in cuticle extension, tensile strength, larval mobility, and body shape.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we found that 37 development‐related unigenes were differentially expressed in larvae compared to adults, for example, storage proteins (lipoprotein and arylphorin), molting regulated proteins (CYP314A1 and ecdysone oxidase), and cuticular protein (Iga & Kataoka, ; Dong et al ., ; Luan et al ., ; Qiao et al ., ; Burmester, ; Li et al ., ). On the other hand, four reproduction‐related unigenes were much more expressed in adults than larvae, among which G1150 encoding vitellogenin had the highest Log 2 FC value of 9.1, as well as the greatest RPKM value (2948) in adult MTs.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, individuals of the F 2 or BC 1 generations were separated by their cuticle pigmentation. Subsequently, their phenotypes were further classified by morphological characteristics, touch feeling, and the ratios between the number of internodes and intersegmental folds in the second, third, and fourth abdominal segments based on an earlier method (Qiao et al . 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction, reverse transcription and Quantitative reverse transcription-PCR (qRT-PCR) conducted as described previously (Qiao et al . 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation